COMT-Val158Met-Polymorphism Is Not a Risk Factor for Acute Kidney Injury after Cardiac Surgery. Issue 2 (7th August 2013) - Kornek, Matthias; Deutsch, Marcus-André; Eichhorn, Stefan; Lahm, Harald; Wagenpfeil, Stefan; Krane, Markus; Lange, Ruediger; Boehm, Johannes
Abstract : Background . Cardiac surgery-associated acute kidney injury (CSA-AKI) depicts a major complication after cardiac surgery using cardiopulmonary bypass (CPB). Objective . CSA-AKI has clearly been linked to increased perioperative morbidity and mortality. Dysregulations of vasomotor tone are assumed to be causal for CSA-AKI. While catechol-O-methyltransferase (COMT) is involved in metabolizing catecholamines, a single-nucleotide polymorphism (SNP) in the COMT gene leads to different enzyme activities according to genotype. Pilot studies found associations between those COMT genotypes and CSA-AKI. Methods . We prospectively included 1741 patients undergoing elective cardiac surgery using cardiopulmonary bypass (CPB). Patients were genotyped for COMT- Val 158 Met -(G/A) polymorphism (rs4680). Results . Demographic characteristics and procedural data revealed no significant differences between genotypes. No association between COMT genotypes and the RIFLE criteria could be detected. A multiple linear regression analysis for postoperative creatinine increase revealed highly significant associations for aortic cross-clamp time (P < 0.001 ), CPB time (P < 0.001 ), norepinephrine (P < 0.001 ), and age (P < 0.001 ). No associations were found for COMT genotypes or baseline creatinine. With anR 2 = 0.39 and a sample size of 1741, the observed power of the regression analysis was >99%. Conclusions . Based on our results, we can rule out an association between the COMT- Val 158 Met -(G/A) polymorphism and the appearance of CSA-AKI.